ZooKeys
ZooKeys is a peer-reviewed, open-access, rapidly produced journal launched to support free exchange of ideas and information in systematic zoology. Papers are published both online and in the traditional printed format, in full compliance with the current requirements of the International Commission on Zoological Nomenclature.